2014
DOI: 10.1016/j.ssci.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of physical and psychosocial risks on employee well-being and quality of life: The case of the mining industry in Ghana

Abstract: While in recent years there has been a growing awareness among mining companies of the need to address physical injuries and environmental issues, there remains a lack of knowledge about how psychosocial risks independently and in conjunction with physical risks affect the health, general well-being and quality of life of mine workers. A cross sectional survey was administered to 330 employees of five large scale mining companies producing three different mineral products (gold, manganese and bauxite) to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 25 publications
(28 reference statements)
3
38
0
Order By: Relevance
“…In term of coping with mental health difficulties, Luthans et al extended the concept of psychological capital to the field of organization and management, with the potential to lead to a positive organizational behavior psychological state in employees, using interventional measures such as cultivating hope and optimism and promoting self-efficacy to improve the mental health and job performance of employees (81). In addition, some studies have focused on the relationship between mental health and QOL; for example, Amponsah-Tawiah et al conducted a case study of the mining industry in Ghana, finding that mining equipment, environmental conditions, and work requirements and control were important predictors of QOL and happiness (82). In recent years, with the continuous acceleration of economic globalization, urbanization and informatization, and the increasing work intensity experienced by employees, "white-collar depression, " and other psychological problems seen in developed countries are also emerging in developing countries such as China and India.…”
Section: Mental Health and Quality Of Lifementioning
confidence: 99%
“…In term of coping with mental health difficulties, Luthans et al extended the concept of psychological capital to the field of organization and management, with the potential to lead to a positive organizational behavior psychological state in employees, using interventional measures such as cultivating hope and optimism and promoting self-efficacy to improve the mental health and job performance of employees (81). In addition, some studies have focused on the relationship between mental health and QOL; for example, Amponsah-Tawiah et al conducted a case study of the mining industry in Ghana, finding that mining equipment, environmental conditions, and work requirements and control were important predictors of QOL and happiness (82). In recent years, with the continuous acceleration of economic globalization, urbanization and informatization, and the increasing work intensity experienced by employees, "white-collar depression, " and other psychological problems seen in developed countries are also emerging in developing countries such as China and India.…”
Section: Mental Health and Quality Of Lifementioning
confidence: 99%
“…Studies show that constructs' internal validity is especially low. Larsson, Pousette, and Törner (2008) use the construct of workplace commitment (Cronbach's alpha = 0.58), and AmponsahTawiah, Leka, Jain, Hollis, and Cox (2014) use the construct of ambient conditions (Cronbach's alpha = 0.56). According to Al-Refaie (2013), Cronbach's alpha of around 0.6 is sufficient for studies of this kind.…”
Section: Structural Equation Modelingmentioning
confidence: 99%
“…Conditions like asthma, silicosis, allergy, deafness, fatigue, lung disease, ocular injuries and certain infectious diseases have been suffered by workers who work in poor and dangerous working environment. [3][4][5][6][7][8] Some occupations are inherently dangerous to health. A report revealed that more than a million workers in the UK suffer from a health condition caused or worsened by the work they do.…”
Section: Introductionmentioning
confidence: 99%